The feasibility and satisfaction study of 5G-based robotic teleultrasound diagnostic system in health check-ups - Ren, Jia-Yu; Lei, Yu-Meng; Lei, Bing-Song; Peng, Yue-Xiang; Pan, Xiao-Fang; Ye, Hua-Rong; Cui, Xin-Wu (Frontiers in Public Health, 2023)
Objective Regular check-up with ultrasound in underserved rural and/or remote areas is hampered due to the limited availability of sonologists and ultrasound devices. This study aimed to assess the feasibility and satisfaction of health check-ups with a 5G-based robotic teleultrasound diagnostic system. Methods In this prospective study, sonologists from two hospitals manipulated the telerobotic ultrasound system to perform teleultrasound check-ups of the liver, gallbladder, pancreas, spleen, kidneys, bladder, prostate (male), uterus and ovaries (female) for the subjects. The feasibility and satisfaction of health check-ups with a 5G-based robotic teleultrasound diagnostic system were evaluated in terms of examination results, examination duration, and satisfaction questionnaire survey. Results A total of 546 subjects were included with the most frequently diagnosed being abdominal disorders (n = 343) and male reproductive illnesses (n = 97), of which fatty liver (n = 204) and prostatic calcification (n = 54) were the most. The median teleultrasound examination duration (interquartile range) for men and women was 9 (9–11) min and 9 (7–11) min (p = 0.236), respectively. All the subjects were satisfied with this new type of telerobotic ultrasound check-ups and 96% reported no fear of the robotic arm during the examination. Conclusion The 5G-based teleultrasound robotic diagnostic system in health check-ups is feasible and satisfactory, indicating that this teleultrasound robot system may have significant application value in underserved rural and/or remote areas to mitigate disparity in achieving health equity.